Influence of rangeland protection and seasonal grazing on aboveground vegetation, forage quality and weight gain of small ruminants — a study in Thar Desert, Pakistan - Islam, Muhammad; Razzaq, Abdul; Hassan, Sawsan; Zubair, Muhammad; Kalroo, Muhammad Waseem; Khan, Attaullah; Gul, Shamim; Ahmad, Sarfraz; Rischkowsky, Barbara; Louhaichi, Mounir (Springer Verlag, 2023)
The Thar Desert, Sindh, Pakistan is characterized by low productivity. Besides, economy is based on agriculture, livestock and mining, nevertheless, livestock graze freely on public and private land. The aim of this research was to determine biomass production and to evaluate the effects of continuous and seasonal grazing on protected and unprotected plots. A 45 ha protected rangeland area of Hurrabad in the Umerkot Thar desert was selected and divided into three blocks of 15 ha each. Blocks of the same size were also established in unprotected area. The data for vegetation biomass, canopy cover, forage nutrients and weight gain of animals in two seasons (spring and summer) was collected from both protected and unprotected sites. The results showed that biomass significantly increased in summer in both sites. However, the biomass values in protected sites were significantly higher. Similarly, the vegetation cover also seemed to increase in summer in both protected (90.7% ± 0.29%) and unprotected sites (39.2% ± 0.09%). The foliar concentrations of all nutrients varied significantly with season. The average final live-weight gain for does on the protected grazing sites during the 42-day period in spring and the 96 days after the monsoon was almost double that of does grazing on the unprotected site during 2016 and 2017 (P < 0.05). The study concludes that the protection of grazing lands during certain periods can lead to better production of vegetation and livestock and improve range conditions.